Presence of anti-nuclear antibody associated with worse clinical outcomes of anti-NMDAR encephalitis - Lei, Chunyan; Li, Yongyu; Li, Haijiang; Zhu, Xiaoyan; Jiang, Wen; Chang, Xiaolong (Frontiers in Neurology, 2022)
Purpose Systemic autoantibodies are important for the diagnosis of autoimmune diseases, but their roles in anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis are unknown. The purpose of our study is to investigate the characteristics and a prognosis of anti-NMDAR encephalitis with the prevalence of autoantibodies. Methods Systemic autoantibodies were evaluated in 64 patients with anti-NMDAR encephalitis and 14 patients with autoimmune encephalitis with other forms. Then, according to systemic autoantibodies, patients with anti-NMDAR encephalitis were divided into an anti-nuclear antibody (ANA) positive group and an ANA negative group. The clinical outcome was assessed by a modified Rankin score at 12 months after the disease onset. Results A total of 64 patients with anti-NMDAR encephalitis were enrolled, of which 28.13% (18/64) were positive for ANA. The titers of a positive anti-NMDAR antibody in CSF (p = 0.041) and serum (p = 0.031) in the ANA-positive group were significantly higher than the ANA-negative group. Patients with ANA positive than those with ANA negative showed lower rates of headache (p = 0.047) and speech disorder (p = 0.049). The presence of ANA was associated with a worse clinical outcome at 12 months (p = 0.043). Conclusion ANA was prevalent in patients with anti-NMDAR encephalitis, and associated with a worse prognosis and impaired neurological recovery.